2015
DOI: 10.1111/afe.12137
|View full text |Cite
|
Sign up to set email alerts
|

Host tissue identification for cryptic hymenopteran parasitoids associated withSirex noctilio

Abstract: 1 Establishing host-parasitoid relationships is challenging for cryptic insects feeding deep in the xylem tissue of trees. Sirex noctilio is a xylophagous feeder and recent invader of North America that co-occurs in pines (Pinus) with a native siricid (Sirex nigricornis) and a suite of shared hymenopteran parasitoids. This insect has a long history as a destructive pest in Southern Hemisphere pine plantations. 2 To establish explicit trophic linkages between native hymenopteran parasitoids and two species of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…All logs (n = 583) were split within 3 months of the initial collection date. PCR assays were used to identify siricid tissue using methods described in Foelker et al (2016b). All live and dead siricid larvae and parasitoid gut contents were identified as S. noctilio.…”
Section: Methodsmentioning
confidence: 99%
“…All logs (n = 583) were split within 3 months of the initial collection date. PCR assays were used to identify siricid tissue using methods described in Foelker et al (2016b). All live and dead siricid larvae and parasitoid gut contents were identified as S. noctilio.…”
Section: Methodsmentioning
confidence: 99%
“…This native parasitoid assemblage is composed of an egg/early instar parasitoid, four late instar rhyssine parasitoids, and a rhyssine cleptoparasitoid. All species have been directly linked to S. noctilio through both observational and molecular means (Foelker et al 2016). The study described here constitutes the most comprehensive evaluation of parasitism of S. noctilio in North America.…”
Section: Discussionmentioning
confidence: 99%
“…They have different fungal symbionts (but see Hajek et al (2013)), emergence phenologies (Ryan et al 2012), and attack trees in different stages of decline (Schiff et al 2012). Despite this, parasitoids appear to have readily adopted S. noctilio as a host (Long et al 2009; Eager et al 2011; Ryan et al 2012; Standley et al 2012; Foelker et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Four species of rhyssines (Ichneumonidae) parasitize later larval instars, and Pseudorhyssa nigricornis (also Ichneumonidae) is a kleptoparasitoid attacking the rhyssines (Foelker and Parry 2021) (Table 1). The biologies of these native parasitoid species are not well understood, although molecular analyses have shown that the rhyssines (analyzed as a group) and I. l. ensiger parasitize both S. nigricornis and S. noctilio (Foelker et al 2016b).…”
Section: Introductionmentioning
confidence: 99%